The Culture of Judicial Independence : Conceptual Foundations and Practical Challenges. - Shetreet, Shimon (BRILL, 2011)
This volume analyzes the development of a culture of Judicial Independence in comparative perspectives, to offer an examination of the conceptual foundations of the principle of judicial independence and to discuss in detail the practical challenges facing judiciaries in different jurisdictions.